Barriers and Facilitators for Safe Sex Behaviors in Students from Universidad de Santiago de Chile (Usach) Through the Com-B Model - Duarte-Anselmi, G; Laroze-Prehn, D (BioMed Central Ltd, 2023)
Background: Unsafe sex is one of the main morbidity and mortality risk factors associated with sexually transmitted infections (STIs) in young people. Behavioral change interventions for promoting safe sex have lacked specificity and theoretical elements about behavior in their designs, which may have affected the outcomes for HIV/AIDS and STI prevention, as well as for safe sex promotion. This study offers an analysis of the barriers and facilitators that, according to the university students who participated in the focus groups, impede or promote the success of interventions promoting healthy sexuality from the perspective of the actions stakeholders should undertake. In turn, this study proposes intervention hypotheses based on the Behavior Change Wheel which appears as a useful strategy for the design of intervention campaigns. Methods: Two focus groups were organized with students from Universidad de Santiago de Chile (USACH). The focus groups gathered information about the perceptions of students about sex education and health, risk behaviors in youth sexuality, and rating of HIV/AIDS and STI prevention campaigns. In the focus groups, participants were offered the possibility of presenting solutions for the main problems and limitations detected. After identifying the emerging categories related to each dimension, a COM-B analysis was performed, identifying both the barriers and facilitators of safe sex behaviors that may help orient future interventions. Results: Two focus groups were organized, which comprised 20 participants with different sexual orientations. After transcription of the dialogues, a qualitative analysis was performed based on three axes: perception about sex education, risk behaviors, and evaluation of HIV/AIDS and STI prevention campaigns. These axes were classified into two groups: barriers or facilitators for safe and healthy sexuality. Finally, based on the Behavior Change Wheel and specifically on its ‘intervention functions’, the barriers and facilitators were integrated into a series of actions to be taken by those responsible for promotion campaigns at Universidad de Santiago. The most prevalent intervention functions are: education (to increase the understanding and self-regulation of the behavior); persuasion (to influence emotional aspects to promote changes) and training (to facilitate the acquisition of skills). These functions indicate that specific actions are necessary for these dimensions to increase the success of promotional campaigns for healthy and safe sexuality. Conclusions: The content analysis of the focus groups was based on the intervention functions of the Behavior Change Wheel. Specifically, the identification by students of barriers and facilitators for the design of strategies for promoting healthy sexuality is a useful tool, which when complemented with other analyses, may contribute improving the design and implementation of healthy sexuality campaigns among university students. © 2023, The Author(s).